COVID-19 Impact on Behaviors across the 24-Hour Day in Children and Adolescents: Physical Activity, Sedentary Behavior, and Sleep - Lauren C. Bates; Gabriel Zieff; Kathleen Stanford; Justin B. Moore; Zachary Y. Kerr; Erik D. Hanson; Bethany Barone Gibbs; Christopher E. Kline; Lee Stoner (Children, 2020)
In the wake of the COVID-19 pandemic, social restrictions to contain the spread of the virus have disrupted behaviors across the 24-h day including physical activity, sedentary behavior, and sleep among children (5–12 years old) and adolescents (13–17 years old). Preliminary evidence reports significant decreases in physical activity, increases in sedentary behavior, and disrupted sleep schedules/sleep quality in children and adolescents. This commentary discusses the impact of COVID-19-related restrictions on behaviors across the 24-h day in children and adolescents. Furthermore, we suggest recommendations through the lens of a socio-ecological model to provide strategies for lasting behavior change to insure the health and well-being of children and adolescents during the COVID-19 pandemic.